Construction of Hierarchical Nanotubes Assembled from Ultrathin V3S4@C Nanosheets towards Alkali‐Ion Batteries with Ion‐Dependent Electrochemical Mechanisms. (3rd January 2020) - Liu, Yang; Sun, Zehang; Sun, Xuan; Lin, Yue; Tan, Ke; Sun, Jinfeng; Liang, Longwei; Hou, Linrui; Yuan, Changzhou
Abstract: Ultrathin core–shell V3 S4 @C nanosheets assembled into hierarchical nanotubes (V3 S4 @C NS‐HNTs) are synthesized by a self‐template strategy and evaluated as general anodes for alkali‐ion batteries. Structural/physicochemical characterizations and DFT calculations bring insights into the intrinsic relationship between crystal structures and electrochemical mechanisms of the V3 S4 @C NS‐HNTs electrode. The V3 S4 @C NS‐HNTs are endowed with strong structural rigidness owing to the layered VS2 subunits and interlayer occupied V atoms, and efficient alkali‐ion adsorption/diffusion thanks to the electroactive V3 S4 ‐C interfaces. The resulting V3 S4 @C NS‐HNTs anode exhibit distinct alkali‐ion‐dependent charge storage mechanisms and exceptional long‐durability cyclic performance in storage of K +, benefiting from synergistic contributions of pseudocapacitive and reversible intercalation/de‐intercalation behaviors superior to those of the conversion‐reaction‐based Li + ‐/Na + ‐storage counterparts. Abstract : Der Kern von V3 S4 @C : Ultradünne Kern‐Schale‐V3 S4 @C‐Nanoblätter, die zu hierarchischen Nanoröhren zusammengesetzt sind, werden für Alkalimetallionen‐Batterien synthetisiert. Vom Alkalimetallion abhängige Mechanismen zur Ladungsspeicherung werden basierend auf systematischen In‐situ/Ex‐situ‐Charakterisierungen und DFT‐Rechnungen vorgeschlagen.